A Child Stunting Against Acute Respiratory Infections in Developing Countries: A Scoping Review - Fadhila, Akbar Kholish; Rahfiludin, Mohammad Zen; Suyatno, Suyatno (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Acute Respiratory Infections (ARIs) are a leading cause of morbidity and mortality among young children, particularly those who experience stunting. This study aims to map the factors associated with ARIs in stunted toddlers using a scoping review methodology. Subjects and Method: This scoping review was conducted using data obtained from PubMed Central. The target population included toddlers with stunting and ARIs. A search was performed using the keywords